Coverage, universal access and equity in health: a characterization of scientific production in nursing - Sara Mendoza-Parra (Universidade de São Paulo, 2016)
Objectives: to characterize the scientific contribution nursing has made regarding coverage, universal access and equity in health, and to understand this production in terms of subjects and objects of study. Material and methods: this was cross-sectional, documentary research; the units of analysis were 97 journals and 410 documents, retrieved from the Web of Science in the category, "nursing". Descriptors associated to coverage, access and equity in health, and the Mesh thesaurus, were applied. We used bibliometric laws and indicators, and analyzed the most important articles according to amount of citations and collaboration. Results: the document retrieval allowed for 25 years of observation of production, an institutional and an international collaboration of 31% and 7%, respectively. The mean number of coauthors per article was 3.5, with a transience rate of 93%. The visibility index was 67.7%, and 24.6% of production was concentrated in four core journals. A review from the nursing category with 286 citations, and a Brazilian author who was the most productive, are issues worth highlighting. Conclusions: the nursing collective should strengthen future research on the subject, defining lines and sub-lines of research, increasing internationalization and building it with the joint participation of the academy and nursing community.